SERAT GATHOLOCO DALAM KAJIAN POSKOLONIAL - Ulum, Muhammad Syahrul (P3M IAIN KEDIRI, 2019)
Literary work is a profound expression of the soul of a writer to describe the existence of his identity. It is not uncommon for a person to express his creative ideas in the literary verses as a symbol of the author to show that his condition is as stated in his work. Also included in the Serat Gatholoco , it is clear that the author is likely to experience one side of his life that is left out. By using imaginary characters he can show his identity. Serat Gatholoco deserves to be studied in scientific research, in this case, researchers use postcolonial studies with qualitative research types. While the primary data in this study are words, phrases, sentences, and paragraphs contained in Serat Gatholoco by Damar Shashangka. The results of this study concluded that in the Serat Case of New Java Literature is loaded with a charge of rebellion due to the arbitrary actions of the superordinate group to the others (liyan) which he considers subordinate. Serat Gatholoco is a reflection of the disgust of those who continually see rigidity in religious life. So those various strategies are used to reverse the binary opposition so that their existence is maintained.